Assessment of Critical Factors Influencing Consumers’ Acceptance of Wearable Sports Devices During COVID-19 Pandemic Conditions - He, Pengfei; Shang, Yunfeng; Ajaz, Tahseen; Nureen, Naila; Sukstan, Wanich (Frontiers in Energy Research, 2022)
Amid rising COVID-19 stringency measures, sedentary behavior has been intensified globally, leading to intense chronic diseases. Due to the potential health benefits associated with digital wearables, there is a dire need to explore the crucial determinants for consumers, which could enhance the usage of sports wearables in addressing health challenges. For this purpose, a novel conceptual framework was developed, and Partial Least Square-Structural Equation Modelling (PLS-SEM) was employed on the primary data of 463 consumers from China. The results revealed a positive association of consumer innovativeness, perceived credibility, perceived ease in using sports wearables, perceived usefulness in using sports wearables, social influence for sports wearables, health benefits, and hedonic motivation for sports wearables during COVID-19 with the adoption intention of sports wearables. The study findings offer valuable policy recommendations to minimize COVID-19 health risks by efficiently monitoring consumers’ health status.